LEGAL ISSUES REGARDING THE ELECTION OF VILLAGE HEADS - Sukman; Rosmini; Insan Tajali Nur (Sekolah Tinggi Ilmu Hukum Awang Long, 2026)
This thesis examines legal issues related to village head elections, with a case study in Kota Bangun 2 Village, Kutai Kartanegara Regency. The background highlights the importance of village head elections in village democracy, but the lack of attention to the village head election regime is a weakness in itself. The results of the study show that violations in Pilkades can be caused by poor supervision, such as administrative disputes and election result disputes. The factors causing Pilkades disputes include internal factors (non-neutral committees, problematic voter lists, unhealthy campaign processes, fanaticism among supporters, and lack of social control) and external factors (local government intervention, regulatory weaknesses, political and power interests, and proximity to local authorities). The mechanism for resolving Pilkades disputes is regulated in Law No. 6 of 2014 concerning Villages, Government Regulation No. 47 of 2015, Minister of Home Affairs Regulation No. 112 of 2014 in conjunction with Minister of Home Affairs Regulation No. 72 of 2020, and Kutai Kartanegara Regency Regulation No. 3 of 2015 in conjunction with Kutai Kartanegara Regency Regulation No. 3 of 2018. However, in practice, the resolution of Pilkades disputes is often not in accordance with the proper mechanisms, as was the case in the Pilkades in Kota Bangun 2 Village.